Lesson Study’s Impact on Early Grade Teachers’ Growth and Pedagogical Knowledge Development - Venketsamy, Roy; Hu, Zijing; Ndlovu, Blanche Ntombizodwa Hadebe; Bipath, Keshni (Universitas Muhammadiyah Surakarta, 2025)
Continuous professional development is vital for enhancing teachers' content knowledge and pedagogical expertise. Research has confirmed that lesson study significantly contributes to improving teachers’ professional development in many Asian countries. This study aimed to explore the impact of the Japanese lesson study model on the professional development of early-grade mathematics teachers. Previous research highlighted that many South African teachers lack adequate content knowledge and pedagogical content knowledge in mathematics instruction, leading to poor learner performance in the subject as revealed in national and international assessments. Using a qualitative case study approach, six early-grade teachers from a school in Gauteng Province were purposively selected as participants. Using Creswell’s six steps of data analysis, the author analysed the data thematically. The findings revealed that, despite their extensive teaching experience, participants lacked knowledge and understanding of mathematical content e and pedagogical content knowledge. However, engagement in collaborative lesson planning, self-reflection, and critical lesson reviews contributed to strengthening their professional development. Additionally, participants reported increased confidence and reduced anxiety when presenting the lessons. They acknowledged that the lesson study approach facilitated their professional growth and enhanced their content and pedagogical knowledge. The study concluded that lesson study is an effective professional development model. Participants emphasised the value of collaborative lesson planning and the formation of communities of practice in fostering learner-centred teaching approaches.